Hubungan Pengetahuan terhadap Kepatuhan Konsumsi Tablet Tambah Darah dengan Kejadian Anemia pada Remaja Putri - Siyami, Ana Soraya; Achyar, Khamidah; Kusuma, Inggar Ratna (Jurnal Riset Kesehatan Masyarakat, 2023)
Anemia is one of the problems of various public health problems that globally affect 1.62 billion people in the world. Anemia in young women is still a big public health problem because the prevalence is still around 20%, which is 21.7%. Anemia status in adolescents is thought to be influenced by several factors, namely knowledge and adherence to taking iron tablets. The purpose of this study was to describe and analyze the relationship between knowledge and adherence to blood supplement consumption with the incidence of anemia in young women. This study used a systematic review design obtained from Google Scholar and PubMed which was then filtered according to inclusion and exclusion criteria. There is a significant relationship between adherence to blood supplement consumption and the incidence of anemia in young women in Indonesia. This means that the more obedient in consuming iron tablets, the female adolescent Hb level will increase. Based on the results of the analysis conducted, it was found that the incidence of anemia in young women was influenced by adherence in taking iron tablets.